Antithrombotic Therapy Duration after Patent Foramen Ovale Closure for Stroke Prevention: Impact on Long-Term Outcome. (27th October 2022) - Kefer, Joelle; Carbonez, Karlien; Pierard, Sophie; Mouthuy, François-Pierre; Peeters, Andre; Hermans, Cedric; Lambert, Catherine; DeMeester, Christophe; Sluysmans, Thierry; Pasquet, Agnes
Abstract : Background . The optimal duration of antithrombotic therapy (ATT) after patent foramen ovale (PFO) closure remains under debate. This study sought to compare the clinical outcome of patients receiving antithrombotic agents for a short (6 months) versus extended (>6 months) period after the procedure. Methods . This was a retrospective cohort study using a propensity score matching analysis on 259 consecutive patients (131 males, 43 ± 10 years) undergoing PFO closure due to cryptogenic stroke, with complete follow-up (median duration of 10 [4–13] years). The outcome was compared between patients receiving short-term (Group short, N  = 88) versus extended ATT (Group long, N  = 171). Results . The PFO closure device was successfully implanted in all cases, with 3% of minor complications. After propensity score matching, there were no differences between Groups short and long in the rate of stroke (0.3 vs. 0.4% patient-year, p = 1.00 ), bleeding (2 vs. 2% patient-year, p = 0.17 ), and device thrombosis (0.3 vs. 0.1% patient-year; p = 0.60 ). Univariate analysis showed that short-term ATT was not associated with an increased risk of recurrent stroke (HR: 1.271 [95% CI: 0.247–6.551], p = 0.775 ) or prosthesis thrombus (HR: 0.50 [95% CI: 0.070–3.548], p = 0.72 ). Kaplan–Meier analysis revealed similar overall survival in Group short and long (100 vs. 99 ± 1%, respectively; p = 0.25 ). Conclusions . Short-term (6 months) ATT after PFO closure did not impair the clinical outcome, with a preserved low rate of recurrent stroke (0.3% patient-year) and device thrombosis (0.2% patient-year) at 10-year follow-up.